Blast Wave Exposure to the Extremities Causes Endothelial Activation and Damage. Issue 5 (November 2015) - Spear, Abigail M.; Davies, Emma M.; Taylor, Christopher; Whiting, Rachel; Macildowie, Sara; Kirkman, Emrys; Midwinter, Mark; Watts, Sarah A.
Abstract : ABSTRACT: Extremity injury is a significant burden to those injured in explosive incidents and local ischaemia can result in poor functionality in salvaged limbs. This study examined whether blast injury to a limb resulted in a change in endothelial phenotype leading to changes to the surrounding tissue. The hind limbs of terminally anaesthetized rabbits were subjected to one of four blast exposures (high, medium, low, or no blast). Blood samples were analyzed for circulating endothelial cells pre-injury and at 1, 6, and 11 h postinjury as well as analysis for endothelial activation pre-injury and at 1, 6, and 12 h postinjury. Post-mortem tissue (12 h post-injury) was analysed for both protein and mRNA expression and also for histopathology. The high blast group had significantly elevated levels of circulating endothelial cells 6 h postinjury. This group also had significantly elevated tissue mRNA expression of IL-6, E-selectin, TNF-α, HIF-1, thrombomodulin, and PDGF. There was a significant correlation between blast dose and the degree of tissue pathology (hemorrhage, neutrophil infiltrate, and oedema) with the worst scores in the high blast group. This study has demonstrated that blast injury can activate the endothelium and in some cases cause damage that in turn leads to pathological changes in the surrounding tissue. For the casualty injured by an explosion the damaging effects of hemorrhage and shock could be exacerbated by blast injury and vice versa so that even low levels of blast become damaging, all of which could affect tissue functionality and long-term outcomes.